Strategy to grow a small and medium enterprise (sme): a case of an islamic fashion company - Febrian Ismet, Rizky; Dung Do, Anh (The Indonesian Journal of Business Administration, 2016)
Abstract. Records from Indonesia central statistical agency (BPS) showed the development of SMEs is growing rapidly in recent years, and making it as one of the economic backbone of the Indonesian economy. In BPS record stated that the contribution of SMEs to Indonesia's GDP is around 60% and it creates very large employment opportunities. One fast growing SMEs industry is the manufacturing industry where one the market is Islamic clothing industry. As a country with the largest Muslim population in the world created the Islamic apparel market has a very attractive of selling value and as evidenced it created of high competitiveness among business Islamic clothing owners from being able to attract buyers. Hence, the condition causes each company requires specific strategies in order to grow and compete in this industry. One of the small categorize company is Fadhila Zahra, which produce and sell Islamic clothing products. With limited capital and resource, the company start having a declining sales and revenue due to improper strategies applied. In this paper the author will provide strategy for Fadhila Zahra Company in order to growth and sustain in the industry by understanding the competitiveness concept, internal and external analysis followed with collecting consumerÃ¢â‚¬â„¢s feedback through questioners and In-depth Interview with other business in the industry. Ã‚Â Keywords: SME, Competitiveness, Business StrategyÃ‚Â